(untitled) (British Journal of Global Ecology and Sustainable Development, 2025)
Uzbekistan has made significant strides toward becoming a more accessible tourism destination, showcasing its beautiful landscapes and rich cultural heritage. The country is working to ensure that people of all abilities can enjoy the same travel experiences, with the goal of becoming a leading global destination.However, challenges remain, including the need for improved infrastructure and better disability identification. Accessible tourism offers both economic and social benefits, such as job creation, increased tourism revenue, and more inclusive communities. While progress has been made, continued efforts to improve infrastructure, laws, and public awareness are essential to ensure that everyone can experience Uzbekistan’s cultural treasures.